PENGEMBANGAN INSTRUMEN ASESMEN PRESENTASI ILMIAH DI SMA - Hilmia Wardani (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
The purpose of this research is to realize a scientific presentation assessment instrument of a high school consisting performance assessment and process assessment instrument. The development of the research used the model developed by Borg and Gall. Trial data collected by document analysis, interviews, and administration of the validator and student questionnaires, then analyzed using qualitative and quantitative techniques. Based on the data of assessment instruments score, scientific presentations was feasible and ready to be implemented.